Are University Students Who Are Taking Philosophy Courses Familiar with the Basic Tools for Argument?. - Iliadi, S.
Philosophy courses help students develop logical reasoning and argument skills or so it is widely assumed. To test if this is actually the case, we examined university students? familiarity with the basic tools for argument. Our findings, based on a sample of 651 students enrolled in philosophy courses at six Greek universities, indicate that students who have prior experience with philosophy are more familiar with the basic tools for argument, and that students who have taken philosophy courses at the university have stronger argument-recognition and argument-evaluation skills compared to university students with no prior experience with philosophy. Moreover, our findings suggest that students get more familiar with the basic tools for argument as their level of engagement with philosophy increases, and that they get significantly better at evaluating arguments when they become graduate students in philosophy. However, our findings also suggest that the majority of students in philosophy classrooms haven?t developed fluency in (at least some) basic argument-related concepts and skills. To remedy this, we argue that philosophy instructors need to re-think (a) the place that the teaching of argument has in philosophy courses, and (b) the way that they teach students about argument.